Local Knowledge Integration in Higher Education in an Online Learning Environment through Virtual Expert Sharing - Darin Jan Tindowen; Jennifer Bangi; Natalie Kate Ramirez; Mica Talay (Journal of Educational Analytics, 2023)
This study was conducted to assess the effectiveness of Project E-LOCAL, a virtual expert sharing activity, in enhancing students’ knowledge and their appreciation on Cagayan culture and tradition of a Private Higher Education Institution in Northern Philippines. A combination of quantitative and qualitative methods of research was utilized in the study. For the quantitative part, both quasi-experimental method and descriptive survey were used, while basic qualitative research was employed from the qualitative aspect of the research. A total of 41 pre-service teachers participated in this study. The results reveal that students have limited knowledge on their own culture prior to the implementation of the program. Finally, results of the evaluation of the students on the implementation of the program shows that Project E-LOCAL is very effective as a teaching and learning strategy in integrating local knowledge in an online learning environment.